Uma experiência docente: o impacto das resoluções da SEDUC-SP (2021-2024) no cotidiano escolar de três escolas periféricas na cidade de Sorocaba - Oliveira, Douglas Silva de (Universidade Federal de São Carlos, 2025)
This study aims to analyze the impacts of the resolutions and regulations implemented by the Department of Education of the State of São Paulo (SEDUC-SP) between 2021 and 2024 on the state public schools E.E. Zélia Dulce de Campos Maia, E.E. Monsenhor João Soares, and E.E. Diógenes de Almeida Marins, located in peripheral regions of the city of Sorocaba. Although presented as innovative and important for the teaching and learning process, they ended up deepening challenges in the school routine, highlighting a clear gap between the State’s discourse and the reality of the schools, especially in peripheral areas, resulting in teacher overload, loss of pedagogical autonomy, and difficulties in student engagement, compromising the quality of education and affecting the school’s transformative role and collective purpose. Thus, the research adopts a qualitative approach, based on the author's direct experience as a teacher, combined with documentary analysis of SEDUC-SP and direct observation in school environments. This methodology enabled a critical analysis of the objectives established by the regulations and the concrete effects observed in the school routine, clearly showing the ineffectiveness of these measures in light of the challenges faced by public education. Among the main obstacles observed are the accumulation of technical tasks, the precariousness of remote learning, pressure for results in standardized assessments, and the growing dependence on private digital platforms. This created a school environment marked by control and competition, devaluing the role of the teacher and the critical development of students. The research, therefore, argues for the need to review these educational policies, promoting dialogue with the school community and valuing the protagonism of teachers and students for a fairer, more participatory education that is more aligned with the reality in which it is embedded.
A teaching experience: the impact of SEDUC-SP resolutions (2021-2024) on the daily school life of three peripheral schools in the city of Sorocaba
Keywords: Educação Pública; Cotidiano Escolar; Políticas Educacionais; Public Education; School Routine; Educational Policies; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA; 4. Educação de Qualidade